Contribution of Islamic Religious Education (PAI) Teachers in Developing the Independent Character of Children with Special Needs at SLB Sukamaju, North Lampung - Hidayah, Wahyudi; Hidayah, Ridho (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2026)
Educators are individuals who show others how to achieve a better life so that their humanity improves according to their nature. The term "character education" is now increasingly popular in Indonesian society. Children with special needs (ABK) are a gift from God, but they have shortcomings because these children have various extraordinary privileges behind their limitations, so they are often considered different. This study aims to explain the responsibilities of teachers in teaching Islamic religion to build the independence of children with special needs, as well as the supporting and inhibiting factors they face in this process at SLB Sukamaju Lampung Utara. This qualitative study used observation, interviews, and documentation to collect information. The data analysis process includes data reduction, data presentation, and drawing conclusions. To verify the validity of the data, techniques of extended observation, increased persistence, data triangulation, and references were used. The results of the study indicate that: 1. The role of Islamic Religious Education teachers at SLB Sukamaju Lampung Utara includes: educators, teachers, and mentors. 2. The role of Islamic Religious Education Teachers in developing independence includes: educating, teaching, guiding, being a model and role model, and conducting evaluations. 3. There are several factors that support the development of independent character in children with special needs at SLB Sukamaju Lampung Utara Special Needs School, including support from the family, the school environment, and the way teachers handle children with special needs with various methods of independent character education, such as lectures and habituation.